2009
DOI: 10.1111/j.1748-0361.2009.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Rural Community‐Dwelling Older Adults

Abstract: If low resilience levels are identified in rural community-dwelling older adults, interventions to build resilience may be helpful in promoting independence; however, further research is needed to determine this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
6
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 24 publications
3
60
6
2
Order By: Relevance
“…Needing support from family was balanced with living in a familiar community with an established social network of friends and neighbours. Social networks consisting of friends rather than family has been shown to contribute to resilience in older people, particularly those in the oldest-old age group living in rural communities (Wells, 2009). This is particularly salient when the reality for many older people living rurally is their families do not live close by (Stockdale, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Needing support from family was balanced with living in a familiar community with an established social network of friends and neighbours. Social networks consisting of friends rather than family has been shown to contribute to resilience in older people, particularly those in the oldest-old age group living in rural communities (Wells, 2009). This is particularly salient when the reality for many older people living rurally is their families do not live close by (Stockdale, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There is also little coverage about the relations between marital status and resiliency (Sołtys, 2013;Wade, Hart, Wade, Bajaj, & Price, 2013;Wells, 2009). Part of the research shows a lack of correlation between marital status and the level of resiliency (Sołtys, 2013;Wells, 2009), while other research suggests that widows are characterized by higher resiliency than divorcees, married women as well as those in separation.…”
Section: Resiliency As a Health Resourcementioning
confidence: 94%
“…Numerous studies have confirmed that employed individuals enjoy better health and more quickly return to a condition typical for them after illness (Bartley, Sacker, & Clarke, 2004;Wells, 2009;Sołtys 2013).…”
Section: Resiliency As a Health Resourcementioning
confidence: 99%
See 2 more Smart Citations